Disorderly Presences - O’Neal, Lauren (InTensions, 2008)
I see my artwork as a collection of unwieldy characters. They possess an inner life of hopes and fears, wonder and mischief, even though they sometimes inhabit the world as unheroic and often disorderly presences-those “late for a very important date” types, who aim to pull it all together but most of the time don’t quite manage. I am interested in what enactment and exaggeration can bring to bear on the slightly uncomfortable dialectic between intimacy and anonymity, movement and stasis, belonging and alienation. I tend to use a mix of found objects, such as chairs and coats, often juxtaposed with commonplace materials including string, tape, and lights, to create a space in which ambiguity and longing act as motors. My sources of inspiration range from business protocol to theatrical set design, where there is a steady rhythm between sameness and difference. The contingent and contextual nature of my work requires that meaning be generated through a series of encounters: between the work and myself, the work and the viewer, or simply the elements of the work in dialogue with each other, ignoring the rest of us completely. Contact: Lauren.ONeal@mcla.edu